Research of Vibration and Noise Analysis Method of High-speed Gear for Electric Vehicle - Ruixin Wang; Chao Yang; Jinfeng Li; Yu Gong; Hongqi Liu; Jingcai Zhang (Jixie chuandong)
Based on the calculation optimization and spectral characteristics of the transmission error， the gear MDOF vibration model is dexterously simplified to a dual-mass vibration model by utilizing the frequency spectrum characteristics of the system transmission error and the frequency characteristics of the forced vibration under excitation. An analytical solution for gear vibration under the excitation of gear transmission error is obtained. A function between the frequency spectrum of gear quality， stiffness and transmission error and the vibration frequency spectrum of gear is established. The key parameters of vibration evaluation， such as gear vibration amplitude， vibration force of tooth， vibration force on bearing and housing are obtained， and the effects of mass， stiffness and transmission error spectrum on vibration are analyzed， which provides a clear and reliable way to analyze and solve the NVH（Noise， Vibration， Harshness） problem of electric vehicle reducer.